Pengamatan Lendutan Vertikal Jembatan Krasak Secara Kontinu dengan Teknologi GNSS - Jaka Putra Sakti; Muhammad Iqbal Taftazani (Universitas Gadjah Mada, 2025)
The Krasak Bridge, located on the border between the Special Region Province of Yogyakarta and Central Java, is the main access between Yogyakarta and Central Java. In accordance with the Regulation of the Minister of Public Works and Public Housing No. 41 of 2015, it is necessary to conduct a feasibility test on this bridge. This study aims to analyze whether the deflection on the Krasak Bridge meets the deflection requirements in RSNI T03 2005. Observations are made directly with the traffic load to get more accurate data, Observations are made at three points, namely TL10, TL20, and TL30, which are located at the two ends and center of the bridge. The method used is rapid static for 15 to 20 minutes, as well as observation of the number of vehicles passing through the bridge along with GNSS measurement. The observation results showed varying changes in elevation/vertical deflection with a maximum deflection of 0.1512 meters in TL10, 0.1760 meters in TL20, and 0.194 meters in TL30. The standard high deviation of kinematic post processing results with RTKLIB software is 1.2 cm. Based on the technical calculation of the bridge loading at RSNI T03 in 2006, the maximum tolerance allowed is 0.28 meters. Therefore, the deflection that occurs on the Krasak Bridge still meets the applicable standards.